Influence of Erosion Potential Analysis Based on Land Use Change in Upper Citarum Watershed - Parhusip, Yemima Gaberiella; Anggraheni, Evi (Universitas Islam 45, 2024)
Population growth and scientific advances have led to increased human needs that can have an impact on the sustainability of the DAS environment. The Citarum River faces a number of problems, including a decrease in water quality due to pollution, depletion of water quantity especially in the dry season, siltation of rivers due to sedimentation and land degradation upstream of the watershed which is reflected in a large range of water discharge. This study aims to find out the rate of erosion related to land use changes in the Citarum Hulu watershed by using the USLE method combined with image interpretation. The results show that the erosion of rain in 2019 was 1017.64 Kj/ha, then the rate of erosion in land use in 2000 was 136.06 tons/ha/year, land use in 2010 was 217.94 tons/ha/year, and land use in 2023 was 186.72 tons/ha/year. The proposed control measures include structural strategies for erosion-prone areas on Citarum Hulu watershed. Thus, the results of the research can be considered by the local government in efforts to manage the watershed.